One-form symmetries in N = 3 S-folds - Amariti, Antonio; Morgante, Davide; Pasternak, Antoine; Rota, Simone; Tatitscheff, Valdo (SciPost physics, 2023)
SciPost Journals Publication Detail SciPost Phys. 15, 132 (2023) One-form symmetries in N = 3 S-folds